Determinan Pertumbuhan Ekonomi ASEAN dalam Perspektif Ekonomi Islam - Huda, Nur; Pratomo, Dimas; Rahman, Taufiqur (IAIN Langsa, 2025)
This study aims to analyze the influence of investment, education, health, and per capita income on economic growth in ASEAN countries during the 2014–2023 period from the perspective of Islamic economics. The contribution of this research lies in integrating Islamic economic principles—such as justice, social welfare, and sustainable development—into the analysis of the determinants of regional economic growth. The methodology employed is panel data regression using the Random Effect Model (REM) approach with the Eviews-10 software. The results show that all independent variables have a positive and significant impact on ASEAN’s economic growth, both partially and simultaneously. These findings reinforce the relevance of Islamic economic values in supporting inclusive and equitable economic policies across the ASEAN region.